Miedzy Panem a plebanem - Michnik, Adam.; Tischner, Jozef; Zakowski, Jacek (Krakow : Znak, 1995)
An interview with two leading Polish political figures who discuss the various intellectual levels and thoughts which have contributed to the recent events in Poland during the last decade.
Includes index.
Keywords: Michnik, Adam -- Interviews; Tischner, Jozef -- Interviews; Poland -- Politics and government -- 1980-1989.; Poland -- Politics and government -- 1989-